Strategi Komunikasi CSR Kopi Jago dalam Membangun Brand Awareness di Kalangan Konsumen dan Komunitas - Mohammad Syahrul Ihsan; Duvalio Adnan Zordi; Tria Patrianti (Institut Nalanda, 2026)
This study analyzes the Corporate Social Responsibility (CSR) communication strategy implemented by Kopi Jago in building brand awareness among consumers and local communities. The approach used is descriptive qualitative, with data collection methods through interviews, observation, and documentation. The results of the study show that Kopi Jago integrates CSR as a strategic communication tool to create emotional closeness with consumers, strengthen community involvement, and increase positive public perception of the brand. The CSR programs implemented, such as social assistance to underprivileged communities, barista training for skill development, and environmental campaigns that support sustainability, contribute significantly to increasing brand recognition, brand recall, and positive associations with the brand. This study also found that transparent, consistent CSR communication based on social values can strengthen the brand's relationship with the community, create loyalty, and increase brand awareness at the local level. Overall, well-planned CSR communication has proven effective in building a positive image and sustainable brand awareness.